2022
DOI: 10.3390/ijerph192315524
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Perceived Social Support on the Mental Health of Homosexuals: The Mediating Role of Self-Efficacy

Abstract: Objective: The purpose of this study was to investigate the mental health of homosexual adults in China and to explore the effects of perceived social support and self-efficacy on mental health. Methods: Two hundred and nine homosexuals were recruited to participate in the online survey. The Perceived Social Support Scale, General Self-efficacy Scale, Self-rating Anxiety Scale and Self-rating Depression Scale were completed through a questionnaire website. Correlation analysis and mediation analysis were used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 49 publications
(69 reference statements)
0
1
0
Order By: Relevance
“…In terms of MSM themselves, intervention programs to enhance social skills and cognitive reframing regarding the self and social relations were found effective to improve their self‐esteem and self‐reinforcement, thus making a difference to their perception of social support (Brand et al., 1995). As for their surroundings, the support from MSM's family and friends might have an impact on MSM's perceived social support (Pan et al., 2022). With deeply ingrained traditional beliefs, some Chinese parents cannot comprehend the homosexual orientation (Ying et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In terms of MSM themselves, intervention programs to enhance social skills and cognitive reframing regarding the self and social relations were found effective to improve their self‐esteem and self‐reinforcement, thus making a difference to their perception of social support (Brand et al., 1995). As for their surroundings, the support from MSM's family and friends might have an impact on MSM's perceived social support (Pan et al., 2022). With deeply ingrained traditional beliefs, some Chinese parents cannot comprehend the homosexual orientation (Ying et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Ambos estudios señalan un alto nivel de apoyo social percibido, tanto para personas que han expresado su homosexualidad como para aquellas que no lo han hecho. Estos resultados contrastan con los de Pan et al (2022), quienes, a pesar de considerar el apoyo social como un factor protector, destacan que los homosexuales no experimentan un nivel elevado de apoyo social percibido. Además, los resultados revelan un nivel de síntomas leves en depresión (Ceballos et al, 2021;Kabir & Brinsworth, 2024).…”
Section: Discussionunclassified
“…Desde un enfoque clínico, la depresión se convierte en un trastorno psicopatológico afectivo que afecta a distintos niveles (González et al, 2019;Villarreal-Zegarra et al, 2019), siendo una de las principales razones de discapacidad a nivel global (Organización Mundial de la Salud [OMS], 2017) y la segunda causa de pérdida de años de vida en Perú (Ministerio de Salud [Minsa], 2006). Por lo tanto, la percepción del apoyo social influye en los síntomas de depresión, transformándose en un factor protector para las personas homosexuales al brindar consuelo y fomentar la adaptación mental (Pan et al, 2022).…”
Section: Introductionunclassified
“…The validity and reliability of the MSPSS have been extensively confirmed through its application in various cultural contexts and populations. With Cronbach's alpha coefficients regularly surpassing 0.85, the scale demonstrates excellent internal consistency, underpinning its efficacy in measuring perceived social support with a high degree of reliability and validity (Özşaker et al, 2015;Pan et al, 2022).…”
Section: Perceived Social Supportmentioning
confidence: 99%
“…For instance, Wang et al (2022) discovered that in patients with recurrent schizophrenia, self-efficacy mediated the relationship between perceived social support and resilience, suggesting that the enhancement of self-efficacy could bolster resilience in this population (Wang et al, 2022). Similarly, Pan et al (2022) identified self-efficacy as a mediator in the relationship between perceived social support and mental well-being among homosexuals, indicating that interventions aimed at increasing selfefficacy could have positive ramifications for mental health (Pan et al, 2022).…”
Section: Introductionmentioning
confidence: 99%